2020
DOI: 10.3390/f11101041
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Export of Dissolved Inorganic and Organic Carbon from a Small Mangrove Estuary with Tidal Fluctuation

Abstract: The significance of aquatic lateral carbon (C) export in mangrove ecosystems highlights the extensive contribution of aquatic pathways to the net ecosystem carbon budget. However, few studies have investigated lateral fluxes of dissolved organic carbon (DOC) and inorganic carbon (DIC), partly due to methodological difficulty. Therefore, we evaluated area-based lateral C fluxes in a small mangrove estuary that only had one exit for water exchange to the coast. We sampled water from the mouth of the creek and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the case of exported OC, DOC remains the major form with DOC : POC of 3.2 ± 0.75, which is higher than the ratios observed globally in mangrove waters (> 1.5; Bouillon et al 2007). In addition, high water discharge due to seasonal typhoons could enhance organic carbon export from mangrove forest (Ohtsuka et al 2020) such was observed in Panay Island where reduction of 40–50% organic matter in eroded mangrove soil was reported after successive severe typhoons in the past (Salmo 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of exported OC, DOC remains the major form with DOC : POC of 3.2 ± 0.75, which is higher than the ratios observed globally in mangrove waters (> 1.5; Bouillon et al 2007). In addition, high water discharge due to seasonal typhoons could enhance organic carbon export from mangrove forest (Ohtsuka et al 2020) such was observed in Panay Island where reduction of 40–50% organic matter in eroded mangrove soil was reported after successive severe typhoons in the past (Salmo 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of carbon export/import fluxes as DOC, POC, and DIC between this study and selected mangroves around the world (unit: mmol m −2 d −1 ).Uncertainties in mean fluxes are linked to seasonal variability in our study site. Data source: Amazon and Brazil: Dittmar and Lara (2001), Dittmar et al (2006); Florida: Romigh et al (2006), Ho et al (2017); Micronesia: Call et al (2019); India: Ray et al (2018); East Australia: Maher et al (2013); NE Australia: Sippo et al (2016); Fly delta, PNG: Robertson and Alongi (1995); Vietnam: Taillardat et al (2018); Japan: Ohtsuka et al (2020); Global mean: Alongi (2020). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the input of pore water via the tidal pump. In mangrove creeks, many studies have shown that the DOC is controlled by the pore water (Bouillon et al, 2007a;Bouillon et al, 2007b;Maher et al, 2013;Pierre et al, 2018;Call et al, 2019;Ohtsuka et al, 2020). During ebb tides, the water that retreats from the tidal creek has a composition similar to that of the pore water, which explains >60% of the DOC and >90% of the DIC (Bouillon et al, 2007a;Maher et al, 2013;Pierre et al, 2018;Call et al, 2019;Ohtsuka et al, 2020).…”
Section: Carbon Dynamics In the Two Creeks In Zhangjiang Estuarymentioning
confidence: 99%